Perfusion of a Kidney Graft From a Donor After Cardiac Death Based on Immediately Started Pulsatile Machine Perfusion-An Experimental Study on a Small Animal - Opatrný, V; Moláček, J; Třeška, V; Matějka, R; Hes, O (Transplantation proceedings, 2018)
INTRODUCTION: There is still a lack of organs for kidney transplantation. The aim of our experimental animal study was to improve the quality of the kidney grafts from donors after cardiac death (DCD) using immediate start of machine perfusion instead of perfusion based on hydrostatic pressure. METHODS: Ten rabbits were used as an experimental model. In group A, 5 kidneys after ischemic injury were perfused in situ using hydrostatic pressure. In group B, 5 kidneys were perfused in situ using machine pulsatile perfusion. After nephrectomy kidney parenchyma was histologically analyzed. We have evaluated the maximum perfusion flow rate, temperature drop rate, and degree of parenchymal injury. RESULTS: The flow rate in the group of machine-perfused animals (group B) was significantly higher than in the control group (group A), and temperature was significantly decreased in group B (P < .001). Qualitative histopathologic evaluation of the perfusion quality of the grafts was statistically significant, again in favor of machine perfusion in group B (P = .005). DISCUSSION: According to our results, the immediate start of machine perfusion is a superior method of kidney graft preservation in DCDs. All observed modalities were superior in the group with machine perfusion compared with usual clinical practice.
Keywords: Animals; Kidney; dárci tkání; Rabbits; transplantáty; Tissue Donors; perfuze; Nephrectomy; transplantace ledvin; uchovávání orgánů; Kidney Transplantation; Pulsatile Flow; modely nemocí na zvířatech; Perfusion; smrt; Disease Models, Animal; Transplants; odběr tkání a orgánů; králíci; Organ Preservation; zvířata; Death; pulzatilní průtok; Tissue and Organ Harvesting; ledviny; nefrektomie